Medical and aesthetic improvement of photodamaged skin by the combination of intense pulsed light and photodynamic therapy with 10% aminolevulinic acid hydrochloride gel. Issue 1 (29th July 2021) - Abrouk, Michael; Dong, Joanna; Waibel, Jill S.
Abstract: Objective: To evaluate the efficacy and safety of photodynamic therapy (PDT) with the novel 10% aminolevulinic acid (ALA) hydrochloride gel (10% ALA gel) and BF‐RhodoLED® light (635 nm; 37 J/cm 2 ) in combination with intense pulsed light (IPL) to augment the medical and aesthetic improvement of photodamaged skin of the décolleté. Methods: This was a single‐site prospective, randomized, intraindividual split chest pilot study with 20 female subjects with moderate to severe photodamage of the décolleté. Subjects were randomized to ALA‐PDT + IPL to one split‐side of the chest and ALA‐PDT only to the contralateral side. Three blinded raters assessed aesthetic improvement using the global aesthetic improvement scale (GAIS). Results: Eighteen subjects completed the study. Superior GAIS results were achieved on the ALA‐PDT + IPL treatment side than on the ALA‐PDT only treatment side ( p  < 0.001) after 24 weeks of follow‐up. Conclusions: ALA‐PDT using 10% ALA hydrochloride gel and BF‐RhodoLED® light had superior rejuvenation effects on the décolleté when combined with IPL compared to ALA‐PDT alone.